Perbaikan Instalasi Pipa Saluran Distribusi Air dan MCK Di Desa Takofi - Said Hi Abbas; Amat Umron; Syamsul Bahri LM; Sandi Rais (Universitas Patria Artha, 2022)
Takofi Village is one of the sub-districts in Moti District. It has an area of 111.39 Km² and is divided into 6 RTs. Because this village is located on the coast, access to clean water and toilet facilities is minimal and unsupportive in terms of health. PKM 2022 activities carried out by the mechanical engineering study program at the Khairun University Faculty of Engineering, one of which is the repair of water distribution pipe installations and toilets, where the current condition of MCK in Takofi village is still inadequate. As for the implementation of repairs to the structure of water distribution channel pipes and toilets, repairs to the installation of water distribution channel pipes and toilets are carried out as well as advice on how to utilize clean water supply and be able to provide a place for waste disposal from toilets so as not to pollute the water, air, and soil in the Takofi village neighborhood. The results of the identification of problems in the implementation of this activity include; a lack of knowledge about the behavior of using MCK, Lack of knowledge about the use of clean water, damage to MCK distribution channel pipes, and improper arrangement of pipe installations, resulting in the malfunction of the water distribution network in MCK..Keywors; Pipeline Installation, Clean Water, MCK, Takofi Village